Identifikasi, Uji Antioksidan, dan Uji Toksisitas Senyawa Bioaktif dalam Caulerpa sertularioides (Vahl.) C. Agard. - Thamrin Wikanta; Swasono R. Tamat; Magdalena Sinta Maryati (JURNAL ILMU KEFARMASIAN INDONESIA, 2006)
Caulerpa sertularioides (Vahl.) C. Agard. is a green seaweed species in the Caulerpaceae family which has been used for medication. Extraction of bioactive compounds from Caulerpa sertularioides have been carried out and screened based on the antioxidative property against DPPH and on toxicity test by the brine shrimp lethality test (BSLT) method. Phytochemical screening of the methanol extract indicated the presence of a triterpen. The methanol extract was partitioned in sequence with n-hexanewater (1:1) and chloroform-water (1:1). The IC50 value of the water extract was found 327 ug/ml and the LCs value was 115 ug/ml as compared to the ICs of vitamin C positive control of 21 ug/ml. Fractination of the water extract in a silica gel column with various ratio of chloroform-methanol did not produce distinct separation. Fractions were analyzed on TLC and fractions of similar components were collected. Fraction I has IC50 value of 326 ug/ml and LC50 value of 68 ug/ml. Further separation and purification of fraction I on a preparative thin layer chromatographic system using chloroform-methanol (50:1) produced five isolates bearing antioxidative activity. The third isolate that showed the strongest activity, when analyzed using a GC-MS system indicating seven compounds, but only [(2-fluorophenyl)methyl)-1H-purin-6-amine that may have an antioxidative activity.